2017
DOI: 10.15547/bjvm.1016
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Coxiella burnetii infection among companion dogs in Fars Province, South Iran

Abstract: Coxiella burnetii is an important zoonosis at a global scale. The epidemiological role of dogs in transmission of Q fever has recently been demonstrated, but there is still a dearth of information on the subject. The aim of present study was to evaluate the occurrence and seroprevalence of Coxiella burnetii infection among companion dogs population in Fars province, South Iran. Blood samples were collected from 181 asymptomatic dogs, mostly referred to Veterinary Hospital of Shiraz University for regular vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Among dogs, two studies reported on C . burnetii prevalence in Iran, yielding a pooled prevalence of 7.7–11% with tick infested dogs that had been referred to the veterinary teaching hospital of Shahid Bahonar University of Kerman having a higher seroprevalence (11%) compared to the 7.7% prevalence reported among asymptomatic companion dogs in Fars province, in the southern part of Iran [ 123 , 137 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among dogs, two studies reported on C . burnetii prevalence in Iran, yielding a pooled prevalence of 7.7–11% with tick infested dogs that had been referred to the veterinary teaching hospital of Shahid Bahonar University of Kerman having a higher seroprevalence (11%) compared to the 7.7% prevalence reported among asymptomatic companion dogs in Fars province, in the southern part of Iran [ 123 , 137 ].…”
Section: Resultsmentioning
confidence: 99%
“…burnetii prevalence in Iran; one among asymptomatic companion dogs in Fars province and the other among dogs taken to a veterinary hospital in Kerman province. From the two studies, a pooled prevalence of 7.7–11% was reported [ 123 , 137 ]. Though Q fever is less prevalent in dogs compared to domestic ruminants, dogs that are exposed to infected wildlife carcasses, sick farm animals and their offspring or livestock environment where the C .…”
Section: Discussionmentioning
confidence: 99%